Pengaruh Kerjasama Tim dan Pengawasan Terhadap Kinerja Pegawai Di Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sikka - Maria Salvani Lebi; Imanuel Wellem; Margaretha Yulianti (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This study aims to: (1) determine the description of employee performance, teamwork, and supervision; (2) analyze the effect of Teamwork and supervision on employee performance either partially or simultaneously.The population in this study were employees of the Sikka Regency Population and Civil Registration Office, totaling 55 people. Because the population is limited, this research was carried out by means of a census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is done through the F test and t test.The results of the descriptive analysis show that the variables of employee performance, teamwork, and supervision are categorized as good. The results of the t-test statistics show that partially the variables Teamwork and Supervision have a positive and significant effect on employee performance. The statistical results of the F test show that simultaneously the variables Teamwork and Supervision have a significant effect on employee performance. The results of the determination analysis show that the two independent variables in this study are able to explain the variation in the ups and downs of the performance of the employees of the Office of Population and Civil Registration of Sikka Regency by 26.99%.